1993
DOI: 10.1080/01904169309364519
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic tripartite nitrogen fixation effectual in eroded soil restoration with 20 year‐ageSericea lespedeza

Abstract: Symbiotic nitrogen fixation is an essential ecological attribute for sustained amelioration of severely eroded, low fertility soils. The long-lived perennial, Sericea (Lespedeza cuneata (Dument) G. Don.), is highly tolerant of depleted soil conditions and has exceptional nitrogen fixation capabilities.Objectives of this study were to determine nodulation characteristics, with adjunctive governing factors, that influence 20 year-age Sericea growth, effectual nitrogen fixation and subsequent improved soil produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…There is some evidence that its residues possess phytotoxic or allelopathic chemicals (Langdale and Giddens, 1967 ; Kalburtji et al, 2001 ), and its residues and root exudates have been found to inhibit seed germination and/or growth of various grass species (Kalburtji and Mosjidis, 1992 , 1993a , b ). In addition to its rhizobacterial symbionts, it has been found to associate with various mycorrhizal fungi in what has been termed a nitrogen-fixing, tri-partite symbiosis (Lynd and Ansman, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that its residues possess phytotoxic or allelopathic chemicals (Langdale and Giddens, 1967 ; Kalburtji et al, 2001 ), and its residues and root exudates have been found to inhibit seed germination and/or growth of various grass species (Kalburtji and Mosjidis, 1992 , 1993a , b ). In addition to its rhizobacterial symbionts, it has been found to associate with various mycorrhizal fungi in what has been termed a nitrogen-fixing, tri-partite symbiosis (Lynd and Ansman, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sericea lespedeza is a perennial, warm-season, herbaceous legume that was introduced in southeastern United States from Japan in 1896 as a potential forage species (Donnelly 1954;Lynd and Ansman 1993). Sericea lespedeza has been planted as a desirable legume for grazing and soil conservation purposes for a number of years and is now found in pastures and along road-sides in southern United States (Guernsey 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the mechanism, it is clear that invasive L. cuneata is disproportionately benefiting from some of the strains surveyed here, while the native L. virginica is not. L. cuneata has previously been reported to associate with mycorrhizal fungi (Lynd and Ansman 1993b;Wilson 1988), and while we are aware of no reports on the mycorrhizal status of L. virginica, a number of other Lespedezas are reported to benefit from arbuscular mycorrhizal fungi (Maki et al 2008;Wu et al 2002). It would be very interesting to know if the disproportionate benefits of L. cuneata reported here extend to these other kinds of symbioses.…”
Section: Asymmetrical Benefit Of Microbial Mutualists To Native and Imentioning
confidence: 99%
“…and nitrogen-fixing bacteria has the potential to alter soil nutrients in the ecosystem (Hawkes et al 2005;Lynd and Ansman 1993a). These soil nutrient changes can lead to vegetation or microbial community alteration (Hawkes et al 2005).…”
mentioning
confidence: 99%